2012
DOI: 10.1128/jb.06341-11
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Domain FlgJ Contributes to Flagellar Hook and Filament Formation in the Lyme Disease Spirochete Borrelia burgdorferi

Abstract: T he bacterial flagellum is a sophisticated macromolecular complex. Its structure and assembly have been well studied in two model organisms, Escherichia coli and Salmonella enterica serovar Typhimurium (for reviews, see references 5, 13, 36, and 58). The flagellum is composed of at least 25 different proteins that can be grouped into three physical parts: the basal body, the flagellar hook, and the filament. The basal body is imbedded within the cell envelope and works as a reversible rotary motor; the flagel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 61 publications
0
28
0
Order By: Relevance
“…We have previously reported that FlgJ from Rhodobacter sphaeroides lacks the muramidase domain (11). At least three studies have been performed that analyzed FlgJ homologues from various bacteria, and it was noticed that various alphaproteobacteria, including R. sphaeroides, possess FlgJ homologues that lack the C-terminal muramidase domain (8,25,39). In R. sphaeroides, FlgJ is similar to the N-terminal part of FlgJ from Salmonella enterica, suggesting that this polypeptide of 100 residues accomplishes the same function as the N-terminal domain of FlgJ from S. enterica, which acts as a scaffolding rod-capping protein (11,13).…”
mentioning
confidence: 99%
“…We have previously reported that FlgJ from Rhodobacter sphaeroides lacks the muramidase domain (11). At least three studies have been performed that analyzed FlgJ homologues from various bacteria, and it was noticed that various alphaproteobacteria, including R. sphaeroides, possess FlgJ homologues that lack the C-terminal muramidase domain (8,25,39). In R. sphaeroides, FlgJ is similar to the N-terminal part of FlgJ from Salmonella enterica, suggesting that this polypeptide of 100 residues accomplishes the same function as the N-terminal domain of FlgJ from S. enterica, which acts as a scaffolding rod-capping protein (11,13).…”
mentioning
confidence: 99%
“…The flagella that reside between the outer membrane and cell cylinder form an elegant ribbon in the periplasmic space as they wrap around the cell cylinder (18)(19)(20)(21)(22)(23)(24). A single periplasmic flagellum is composed of a motor (FliF and many other proteins), hook (FlgE), and filament (FlaB and FlaA) (25)(26)(27). B. burgdorferi flagellar filaments consist of a major FlaB and a minor FlaA protein comprising 10 to 14% and less than 0.5% of total cellular protein, respectively (28,29).…”
mentioning
confidence: 99%
“…(B to D) Determination of the stability of BB0569 in the wild type (B) and the ⌬mcp 2 (C) and ⌬mcp 3 (D) mutants. The assay was carried out as previously described (38). Translation of B. burgdorferi was arrested by adding spectinomycin (100 g/ml) to the cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoblots were developed with the horseradish peroxidase-labeled secondary antibodies by using the Pierce ECL Western blotting substrate kit (Thermo Scientific, Rockford, IL). Densitometry of immunoreactive proteins in the blots was used to determine the relative amounts of proteins, as previously described (38). Densitometry was measured by using the Molecular Imager ChemiDoc XRS imaging system (Bio-Rad, Hercules, CA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation